2015
DOI: 10.1186/s13104-015-1237-2
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics in stroke patients with atrial fibrillation: clinical trials versus clinical practice

Abstract: BackgroundWhen applying information gathered from medical research to the clinical setting, it is imperative that the sample of the investigated patients be representative of the clinical population. Because of this fact, it is necessary to closely examine the sample’s baseline characteristics in clinical trials.MethodsWe analysed baseline data of relevant trials investigating considerable proportions of patients with atrial fibrillation (AF) in the secondary stroke prevention: EAFT, SIFA, Active-W, BAFTA, RE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Moreover, real-world fragile patients might have been included (e.g., patients with increased risk of bleeding, liver disease, and chronic kidney disease), although these patients would be less represented in the trials. 10) This paper highlights recently published real-world data of NOACs and further recommends NOAC dosages for Korean patients.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, real-world fragile patients might have been included (e.g., patients with increased risk of bleeding, liver disease, and chronic kidney disease), although these patients would be less represented in the trials. 10) This paper highlights recently published real-world data of NOACs and further recommends NOAC dosages for Korean patients.…”
Section: Introductionmentioning
confidence: 93%
“…Christian Tanislav et al reported the higher mean age and overrepresentation of male sex in the baseline characteristics of stroke patients [39]. In a study conducted by Ginenus Fekadu et al, the number of males found to be higher consisted of 62.9% among the overall stroke patients [40].…”
Section: Discussionmentioning
confidence: 97%
“…Связь между АГ и ФП -двунаправленная [18]. Недавние клинические исследования показали, что у лиц с ФП в 70,7-85,0% случаев регистрируется АГ [18][19][20]. По данным российского регистра РЕКВАЗА, 90,5% лиц с ФП имеют АГ [21].…”
Section: эпидемиологияunclassified